EXTENDED CONSTANT RANK CONDITION AND ITS APPLICATION TO PARAMETRIC OPTIMIZATION PROBLEMS - S. V. Aktanorovich; L. I. Minchenko; A. N. Tarakanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Extended constant rank condition is introduced and its applications to the sensitivity analysis of parametric nonlinear programming problems are studied.